THE SEISMIC RESPONSE OF STRUCTURAL OUTRIGGER SYSTEMS IN TALL BUILDING: الاستجابة الزلزالية لأنظمة المدادات الهيكلية في المباني العالية - el-gharbawy, eman; Husain, Mohamed; Hassan, Hilal; Mohamed, Heba; el-gharbawy, eman (Journal of Applied Engineering Science, 2021)
One of the advanced structural systems that have been applied in tall buildings to improve the building strength during quake loads is the outrigger system. For that, this research is interested to study different structural system as a vierendeel system and wall beam system when applied them as outrigger which is connected between the internal core walls and the external columns in one or two stories. The outrigger position changed through the tallness of 40 story building and the building response is examined in this research under El-Centro time history earthquake load. All the models are analyzed in Midas-Gen program and the research conclusions were concluded to help researchers to provide more in the field of civil engineering. The inferred parameters as storey drift, story drift ratio and base storey overturning moment are plotted in graphs between the storey number and the outrigger position for each outrigger system. The results showed that, the one storey wall beam structural system is better than two stories vierendeel structural system when these systems applied as outrigger system. The best position for one storey outrigger is about 0.45 of the total building height and for the two stories outrigger, the .20 and .45 of the total building height are the best positions. Overall, the outrigger system is an effective structural system to make the tall buildings withstand through the earthquake loads.